Distinct stress‐related medial prefrontal cortex activation in women with depression with and without childhood maltreatment. Issue 4 (24th January 2022) - Dong, Daifeng; Belleau, Emily L.; Ironside, Maria; Zhong, Xue; Sun, Xiaoqiang; Xiong, Ge; Cheng, Chang; Li, Chuting; Wang, Xiang; Yao, Shuqiao; Pizzagalli, Diego A.
Abstract: Background: Emerging evidence has highlighted the moderating effect of childhood maltreatment (CM) in shaping neurobiological abnormalities in major depressive disorder (MDD). However, whether neural mechanisms underlying stress sensitivity in MDD are affected by the history of CM is unclear. Methods: Two hundred and thirteen medication‐free female participants were recruited for a functional magnetic resonance imaging study assessing the effects of psychosocial stress on neural responses. The Montreal Imaging Stress Task was administrated to 44 female MDD patients with CM (MDD/CM), 32 female MDD patients without CM (MDD/noCM), 43 female healthy controls (HCs) with CM (HC/CM), and 94 female HCs without CM (HC/noCM). A CM (CM, noCM) × diagnosis (MDD, HC) whole‐brain voxel‐wise analysis was run to assess putative group differences in neural stress responses. Results: A significant CM × Diagnosis interaction emerged in the medial prefrontal cortex (mPFC). Bonferroni‐corrected simple effects analysis clarified that (1) the MDD/CM group had less mPFC deactivation than the HC/CM group, (2) the MDD/noCM group exhibited greater mPFC deactivation than the HC/noCM group, and (3) the MDD/CM group exhibited less mPFC deactivation relative to the MDD/noCM group. In addition, the mPFC‐seed psychophysiological interaction analysis revealed that individuals in the CM groups had significantly greater stress‐related mPFC‐left superior frontal gyrus and mPFC‐right posterior cerebellum connectivity relative to the noCM groups. Conclusions: Findings highlight distinct neural abnormalities in MDD depending on prior CM history, particularly potentiated stress‐related mPFC recruitment among MDD individuals reporting CM. Moreover, CM history was generally associated with the disruption in functional connectivity centered on the mPFC.